2020
DOI: 10.1136/thoraxjnl-2019-214204
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival following initiation of home non-invasive ventilation: a European study

Abstract: IntroductionAlthough home non-invasive ventilation (NIV) is increasingly used to manage patients with chronic ventilatory failure, there are limited data on the long-term outcome of these patients. Our aim was to report on home NIV populations and the long-term outcome from two European centres.MethodsCohort analysis including all patients established on home NIV from two European centres between 2008 and 2014.ResultsHome NIV was initiated in 1746 patients to treat chronic ventilatory failure caused by (1) obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…This 2021 CTS CPG update constitutes a significant shift in the approach to long-term NIV in patients with COPD and chronic hypercapnic respiratory failure, moving from a 2011 recommendation of not using it in most circumstances to a weak/conditional but favorable recommendation supporting its use in this specific context. 15 Considering the high prevalence of COPD, which is now one of the most common reasons to initiate long-term NIV in many jurisdictions, [12][13][14] this revised recommendation may place a high burden on the already scarce sleep laboratory and respiratory home-care resources in Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 2021 CTS CPG update constitutes a significant shift in the approach to long-term NIV in patients with COPD and chronic hypercapnic respiratory failure, moving from a 2011 recommendation of not using it in most circumstances to a weak/conditional but favorable recommendation supporting its use in this specific context. 15 Considering the high prevalence of COPD, which is now one of the most common reasons to initiate long-term NIV in many jurisdictions, [12][13][14] this revised recommendation may place a high burden on the already scarce sleep laboratory and respiratory home-care resources in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…This is in sharp contrast with many European countries where chronic hypercapnic respiratory failure associated with COPD is one of the most frequent indications for the initiation of long-term NIV. [12][13][14] Since the 2011 publication of the Canadian Thoracic Society (CTS) Clinical Practice Guideline (CPG) for home NIV, 15 important clinical trials have revealed new information necessitating an update to the current recommendations for NIV in COPD. This revised CPG deals specifically with chronic hypercapnic respiratory failure due to advanced COPD as opposed to other possible confounding conditions such as sleep apnea or obesity-related hypoventilation.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A recent study found that patients with obstructive airway disease were more likely to have their HMV set up following an acute admission (70%) than other diseases. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The single most important factor associated with a poor outcome was low adherence (NIV use < 4 h per day). 21 For this reason, we recommend adaptation of adherence criteria as proposed in the other TEP reports, including the second 90-day trial period for those patients not meeting initial adherence criteria for continued coverage who return at least twice to a treating physician and see benefit from continued use. Rehospitalization would constitute criteria for a new HMV initiation trial even in those previously failing to meet adherence criteria.…”
Section: Current Evidence/guidelinesmentioning
confidence: 99%